An extremely rare case of adrenocortical cancer with cannon ball pulmonary metastasis - Falcone, Vito Antonio; Nardi, Ilaria; Mesto, Maria; Trotta, Vanessa; Picca, Vito (Monaldi Archives for Chest Disease, 2019)
Multiple pulmonary nodules on chest X-ray, known commonly as cannon ball secondaries, are the classical presentation of hematogenous dissemination of a malignant tumor to the lungs. This almost always indicates an advanced stage of the disease with a very grim outlook in terms of cure or survival. In this case report, we present a patient with very extensive cannon ball lung metastases due to adrenocortical carcinoma with a more favorable prognosis. This is the first case described in the literature of cannonball lung metastases from adrenocortical tumor in a man.